Low-dose methotrexate-induced vulvar edema: A case report. Issue 35 (August 2019) - Jia, Guifeng; Chai, Wei; He, Zhiwei; Liu, Xiaojing; Wen, Yan; Cui, Lifeng; Gong, Fengyan
Abstract: Rationale: Methotrexate (MTX) is an antimetabolite of folic acid, which is used for management of ectopic pregnancy. MTX-related toxicity may include cutaneous mucosal damage, bone marrow suppression, gastrointestinal disorders (gastritis, diarrhea, hematitis), liver and kidney function damage, pulmonary toxicity, cardiac toxicity, and nerve toxicity. However, it is not usual for vulvar edema induced by low-dose methotrexate. Patient concerns: In this case report, we described a patient with severe vulvar edema and oral cavity ulceration and scalp ulceration induced by low-dose MTX treatment for ectopic pregnancy. Her presenting complaints were pain in the vulva, oral cavity, and scalp. Diagnoses: The patient was diagnosed based on clinical findings for MTX toxic reactions. Interventions: Vulva was disinfectioned with iodide and Kangfuxin solution, her mouth was rinsed with mouthwash. Three compound glycyrrhizin tablets were orally administered (3 times/day). After 10 days, the broken skin and mucous membrane healed. Outcomes: The vulvar edema and oral cavity ulceration and scalp ulceration healed. Lessons: Our study demonstrated that even low-dose MTX can be induced skin and mucosal injury, patients and doctors should timely detection of drug toxicity reactions, immediately rescue, prompt discontinuation of medication, and symptomatic treatment to avoid accidental occurrence.